Detailed long‐term hydro‐thermal scheduling for expansion planning in the Nordic power system. Issue 2 (1st November 2017) - Helseth, Arild; Mo, Birger; Lote Henden, Arild; Warland, Geir
Abstract : The authors describe a method for long‐term hydro‐thermal scheduling allowing treatment of detailed large‐scale hydro systems. Decisions for each week are determined by solving a two‐stage stochastic linear programming problem considering uncertainty in weather and exogenous market prices. The overall scheduling problem is solved by embedding such two‐stage problems in a rolling horizon simulator. The method is verified on data for the Nordic power system, studying the incremental changes in expected socio‐economic surplus for expansions in both the transmission and generation systems. Comparisons are made with a widely used existing long‐term hydro‐thermal scheduling model. The results indicate that the model is well suited to valuate the flexibility of hydropower in systems with a high share of intermittent renewable generation.